The unusual cytoarchitecture of “vitelline follicles” in freshwater blood flukes of the genus Sanguinicola (Digenea, Aporocotylidae) - Poddubnaya Larisa G.; Zhokhov Alexander; Gibson David I. (Parasite, 2021)
This is the first study assessing the cytoarchitecture of the vitellarium of members of the freshwater, teleost-infecting lineage of blood-flukes (Aporocotylidae). The vitelline cytoarchitecture of two innominate species of Sanguinicola from freshwater fishes in Russia showed that vitelline cells at different stages of maturation are widely distributed throughout much of the body and are mixed with other cell types. The latter feature indicates that use of the term “follicular vitellarium” is inappropriate for species of this genus. An additional characteristic of the vitelline cells in these Sanguinicola spp. is their ability to form long, pseudopodia-like extensions of the peripheral cytoplasm that contact neighbouring vitelline cells and sarcoplasmic extensions, forming both heterologous and homologous intercellular junctions. Within the vitelline duct lumen, the cytoplasm of mature vitelline cells is filled with regular clusters (0.5–1.0 μm in diameter), comprising 10–30 vitelline globules, which have heterogeneous contents and electron-lucent lipid droplets (1.1–1.7 μm in diameter), but no apparent modifications of vitelline globules occur within the vitelline duct. The flattened, ciliated, epithelial lining of the common vitelline duct contains intra-epithelial nuclei, its luminal surface bears shallow lamellae and adjacent cells are adjoined by apical septate junctions. All of these observations, when compared to the marine Aporocotyle simplex, likely represent additional characteristics supporting the divergent evolutionary lineages of marine and freshwater aporocotylids.